2017
DOI: 10.1097/hco.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on heart failure

Abstract: Obesity is strongly associated with the development of heart failure, through direct and indirect mechanisms. Although clear consensus regarding weight reduction in this patient population is lacking, there is mounting clinical evidence that intentional weight loss may be beneficial, in spite of the well-recognized obesity paradox, particularly as the presence of obesity presents unique challenges in the advanced therapy of heart failure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 96 publications
2
32
0
4
Order By: Relevance
“…9 It is currently known that, in severe obesity, cardiac output is increased at the expense of increased circulating volume, leading to a state of chronically elevated preload, which favors the increase of ventricular dimensions, of parietal stress and LV mass. 8,12,14,25,26 This set of chronic hemodynamic changes can lead to cardiac structural impairment with cardiac performance loss.…”
Section: Hemodynamic and Morphological Changes Associated With Obesitymentioning
confidence: 99%
See 3 more Smart Citations
“…9 It is currently known that, in severe obesity, cardiac output is increased at the expense of increased circulating volume, leading to a state of chronically elevated preload, which favors the increase of ventricular dimensions, of parietal stress and LV mass. 8,12,14,25,26 This set of chronic hemodynamic changes can lead to cardiac structural impairment with cardiac performance loss.…”
Section: Hemodynamic and Morphological Changes Associated With Obesitymentioning
confidence: 99%
“…20 In addition to correlating with obesity, that change correlates with obesity duration. 8 The Framingham Heart Study has shown that BMI is an independent predictor of LV mass, mainly when BMI exceeds 30 kg/m 2 . 14 The literature is highly controversial regarding the LVH pattern related to obesity.…”
Section: Hemodynamic and Morphological Changes Associated With Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…The relation between obesity and heart failure (HF) is complex. Although obese people have twice the risk to develop HF, obesity is protective in patients with established HF, a phenomenon termed “the obesity paradox.” 14 Despite this, many of these patients proceed to stage D HF. Morbid obesity (defined as a body mass index (BMI) ⩾ 35 kg/m 2 ) is a limitation to candidacy for heart transplantation (HTx) and those who are obese (defined as a BMI ⩾ 30 kg/m 2 ) and undergo HTx have worse outcomes.…”
Section: Introductionmentioning
confidence: 99%